Penyuluhan Literasi Digital Bagi UMKM Lokal Berbasis Media Sosial di Villa Gading Harapan RW. 021 Kelurahan Kebalen - Mugiarso (VIDHEAS: Jurnal Nasional Abdimas Multidisiplin, 2024)
Digital literacy outreach is crucial for MSMEs to optimize product marketing in the digital era. This program aims to enhance the understanding and skills of MSME players in Villa Gading Harapan RW 021 in using social media platforms for digital marketing. The approach involves training and mentoring on WhatsApp Business, Instagram, and Facebook to create effective marketing strategies. Participants learned to manage business accounts, produce engaging content, and interact with customers using features like WhatsApp catalogs, Instagram Stories, and Facebook Pages. The program started with basic training on digital literacy and social media use, followed by practical sessions on creating visual content, using hashtags, and managing advertisements. Despite challenges like limited technical skills and content creation difficulties, participants showed enthusiasm and actively applied the knowledge gained. They created promotional content, handled customer interactions, and analyzed market feedback. Networking among MSMEs also grew, fostering collaboration and experience sharing. Evaluation showed significant improvements in participants' digital marketing skills, leading to increased customers and sales. A digital MSME community was formed to ensure the program's sustainability, serving as a model for similar initiatives in other areas.